REVIVING BLORA'S CULTURE: AN AUGMENTED REALITY MODULE BASED ON ART AND TRADITION FOR COLLEGE STUDENTS' ENGLISH LEARNING - Imro'athush Sholihah, Husna (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2026)
This study responds to the growing need for culturally grounded and technology-enhanced English learning materials for students enrolled in Primary School Teacher Education programs. At the university level, English instruction often remains generic and insufficiently connected to the cultural contexts that prospective elementary school teachers are expected to introduce in their future classrooms. Addressing this gap, the present study aims to develop an English learning module that integrates local arts and traditions from Blora with Augmented Reality, thereby enhancing contextual relevance, learner engagement, and motivation. The research adopts a development-oriented approach comprising three main stages: needs analysis, product design, and prototype development. Data were collected through interviews, questionnaires, and expert validation processes. The findings from the needs analysis reveal a clear demand among both lecturers and students for English learning materials that are contextually meaningful and supported by interactive technological features. The resulting prototype incorporates local cultural elements, including Barongan and Tayub, which are presented through interactive Augmented Reality components to facilitate more immersive learning experiences. Validation results indicate that the module is highly feasible in terms of content quality and feasible in terms of media design. These findings suggest that the integration of local cultural content with interactive technology not only enriches instructional materials but also fosters more meaningful and engaging English learning experiences.